The Process We Call Earth: Relationships Between Dynamic Feedbacks and the Search for Gaiasignatures in a New Paradigm of Earthlikeness - Michael L. Wong; Marissa Duckett; Emilia S. Hernandez; Vahab Rajaei; Kayla J. Smith (Perspectives of Earth and Space Scientists)
Abstract Standard notions of an “Earthlike” planet rely solely on physical and material properties, like planetary mass, radius, and surface temperature. Here, we introduce a novel, relational perspective on what defines “Earthlikeness.” In our process‐based framework, rocky planets are local pockets of free energy that have the potential to drive the emergence of dynamically persistent systems that coevolve with one another. Examples of dynamically persistent planetary phenomena include magnetic dynamos, mantle convection, tectonic regimes, deep volatile cycles, global climate feedbacks, biogeochemical cycles, and the biosphere. When two or more processes couple to one another such that they gain causal efficacy over one another's persistence, some degree of planetary‐scale homeostasis may emerge. In astrobiology, Earthlike exoplanets are often considered to be priority targets for the search for life elsewhere. We suggest that a process‐based framework for Earthlikeness has the potential to widen our search space and inspire novel planetary‐scale biosignatures, or “Gaiasignatures,” that may be essential for detecting exoplanetary biospheres. Additionally, a process‐based view of life can influence the development of agnostic biosignatures at all scales. In contrast to the dominant scientific perspective, which has tended to engender a materialistic worldview, relational ontologies may contribute to our scientific understanding of Earth as a network of dynamically persistent systems, humanity as an integral part of nature, and the search for life in the universe.